Peningkatan Kepuasan Pasien Bpjs Rawat Jalan Claster 2 KIA Melalui Penguatan Mutu Pelayanan Di Puskesmas Bunut - Isra Filyani; Toni Toni; Kiswanto Kiswanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Community Health Centers (Puskesmas) play an important role as primary healthcare facilities in providing services for National Health Insurance (JKN) participants, particularly outpatient services in the Maternal and Child Health (MCH) cluster. Service quality is a key factor influencing patient satisfaction among BPJS Health participants. This residency activity aimed to analyze the effect of service quality on patient satisfaction among BPJS outpatient clients in Cluster 2 MCH at Bunut Health Center. A qualitative case study approach was employed through observation, in-depth interviews, focus group discussions, and document review. Informants consisted of BPJS patients, the head of the health center, and healthcare workers. The results indicated that MCH service quality had not been optimal, particularly in terms of limited human resources, inefficient service flow, and inadequate supporting facilities. External factors such as community knowledge and economic conditions also influenced patient satisfaction. Therefore, continuous efforts to improve service quality, strengthen human resources, and optimize service systems are necessary to enhance patient satisfaction among BPJS outpatients in the MCH cluster.